Preparation and application of angstrom confinement electrocatalyst for selectively activating molecular oxygen to produce hydroxyl radicals
By supporting metal single atoms and alkali metal cations in the 2H phase MoS2 catalyst, a 1T phase MoS2 catalyst is formed, and the Amy-limited space is constructed, which solves the problem of low mass transfer efficiency of hydroxyl radicals in the prior art, and achieves efficient generation and utilization of hydroxyl radicals, and improves the removal efficiency of water pollutants.
Patent Information
- Application Number
- CN202510130449.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-05
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2045-02-05
AI Technical Summary
The prior art is difficult to effectively utilize hydroxyl radicals in water pollution treatment, resulting in low mass transfer efficiency and insufficient reaction capacity, limiting its actual utilization rate in heterophasic reactions.
By designing and optimizing the Amy domain confined electrocatalyst, using 2H phase MoS2 as a precursor, supporting metal single atoms and alkali metal cations, a 1T phase MoS2 catalyst is formed, and the Amy domain confined space is constructed, which significantly improves the generation rate and utilization efficiency of hydroxyl radicals.
It realizes efficient generation and utilization of hydroxyl radicals, significantly improves the removal efficiency of target pollutants, has good electrochemical stability and a simple preparation method.
Smart Images

Figure CN119549169A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of novel electrocatalysts, and in particular to the preparation and application of an angstrom-confined electrocatalyst for selectively activating molecular oxygen to produce hydroxyl radicals. Background Art
[0002] The confinement effect of nano-confinement, which restricts the reaction to nanoreactors (such as interfaces, channels, cavities and pores), has attracted great attention because it can significantly improve the intrinsic properties of the catalytic system (such as electronic structure, mass transfer, electron transfer, phase state and reaction rate). From a thermodynamic point of view, according to Le Chatelier's principle, the reaction equilibrium can be changed by enriching and concentrating the reactants or removing the products, thereby accelerating the reaction rate. Therefore, the electron distribution on the catalyst surface can be regulated by the nano-confinement effect, thereby improving the activity, selectivity and stability of the catalytic system. In recent years, significant progress has been made in the application research of nano-confinement effect in the environmental field (including adsorption and membrane technology). Theoretical predictions show that the catalytic performance of angstrom-scale confined catalysts is better than that of traditional nano-confinement due to stronger electronic interactions, more precise spatial positioning, and more efficient diffusion and reaction processes. Although angstrom-confined catalysis (ACC) is very attractive in fields such as water treatment, its practical application still faces many challenges. For example, the precise construction of angstrom-scale channels, the uniform distribution of catalytic active centers at the angstrom scale, and the balance between stability and activity have limited the further promotion of ACC technology.
[0003] Two-dimensional (2D) structures are considered to be ideal materials for enhancing the diffusion paths of reactants due to their high exposed specific surface area and abundant active sites. Due to the inherent van der Waals interactions in the interlayer space, layered 2D structures are optimal angstrom-confined reactors for fixing various active sites such as metals, small organic molecules, and polymers. In addition, the huge capillary action (>50 bar) in the nanochannels of 2D materials can significantly accelerate the molecular transport process. Therefore, layered structures assembled from 2D materials can be used as angstrom-confined spaces for water pollution treatment. In particular, molybdenum disulfide (MoS2) nanosheets, which have emerged in recent years, have attracted widespread attention due to their unique electrical, physicochemical, biological, and mechanical properties. MoS2 nanosheets have been widely used in electronic devices, catalysis, biomedicine, and energy-related fields, and will also show important potential in the environmental field. Generally, 2H phase MoS2 has semiconductor properties with a band gap ranging from 1.3-1.9 eV, depending on the interlayer thickness; in contrast, 1T phase MoS2 exhibits obvious metallic properties with an electronic conductivity of about 10 of that of the 2H phase. 7The unique structure and electronic properties of MoS2 make it possible to precisely control catalytic reactions, laying a solid foundation for breakthroughs in environmental catalysis technology, and are of great significance for selectively activating molecular oxygen to generate reactive oxygen species (ROS) within the angstrom scale.
[0004] Water pollution poses a serious threat to human health and aquatic ecosystems, so the development and implementation of efficient wastewater treatment technologies are essential to eliminate pollutants. Although antibiotics play an important role in improving human health, their potential harmful effects on aquatic ecosystems and human health, as well as the risk of the spread of antibiotic resistance in ecosystems, pose even more severe challenges to environmental remediation. Electro-Fenton technology has attracted widespread attention due to its unique advantages. This technology uses O2 as a reactant for a two-electron oxygen reduction reaction, and uses in-situ generated hydrogen peroxide to further activate ROS (including: hydroxyl radicals (HO • ), superoxide radicals (O2 •- ), singlet oxygen, etc. ( 1 O2)), shows great potential in the degradation of organic pollutants. It is worth noting that hydroxyl radicals have become an ideal oxidant for the degradation of organic pollutants in the environmental field due to their strong oxidizing property (oxidation potential up to 2.80 V). However, the life span of free radicals is short (10 -6 ~10 -9 s) limits the mass transfer efficiency from the catalyst surface to the solution where the target pollutant is located, which seriously limits the actual utilization rate of free radicals in heterogeneous reactions. In addition, free radicals inevitably react with dissolved organic matter and coexisting inorganic ions in the water matrix, thereby significantly reducing their reactivity with target pollutants. These problems show that the intervention of Angstrom confinement technology is urgently needed. By designing and optimizing Fenton-like heterogeneous catalytic systems, the effective utilization rate of free radicals can be significantly improved, providing innovative solutions for water pollution control. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a preparation and application of an angstrom-confined electrocatalyst for selectively activating molecular oxygen to produce hydroxyl radicals. The angstrom-confined catalyst provided by the present invention has high three-electron selectivity, can significantly expose catalytic active sites, accelerate the mass transfer of reactants, and produce active oxygen species in a penetration reactor, achieving high hydroxyl radical generation rate and utilization efficiency in the angstrom channel, and has a simple preparation method and good electrochemical stability. The present invention lays the foundation for angstrom-confined catalysis and reflects the importance of angstrom-confined strategy in the design of efficient catalysts for water pollution control.
[0006] The first object of the present invention is to provide an angstrom-confined catalyst for selectively activating molecular oxygen to produce hydroxyl radicals, using 2H phase MoS2 as a precursor, the surface of the precursor is loaded with metal single atoms and intercalated with alkali metal cations; the angstrom-confined catalyst is 1T phase MoS2 loaded with metal single atoms.
[0007] In some embodiments of the present invention, the metal single atom is one or more of iron, cobalt, nickel, and copper; further, preferably iron single atom; the definition of metal single atom in the present invention can be summarized as: the active metal in the catalyst is uniformly dispersed on the carrier in the form of single atoms, and there is no interaction in any form between each individual atom. The surface of the precursor prepared by the present invention forms single atoms, such as single atoms Fe, Co, Ni, Cu, etc., and the metal single atoms are loaded on the MoS2 carrier.
[0008] The alkali metal cations include one or more of lithium ions, sodium ions, and potassium ions.
[0009] In some embodiments of the present invention, the loading amount of the metal single atom is 0.5-3.0 wt%, and illustratively, it can be 0.5 wt%, 1.0 wt%, 1.5 wt%, 2.0 wt%, 2.5 wt%, 3.0 wt%, etc.; the loading amount of the alkali metal cation is 0.5-3.0 wt%, and illustratively, it can be 0.5 wt%, 1.0 wt%, 1.5 wt%, 2.0 wt%, 2.5 wt%, 3.0 wt%, etc.
[0010] The second object of the present invention is to provide a method for preparing the Angstrom-confined catalyst for selectively activating molecular oxygen to produce hydroxyl radicals, comprising the following steps: (1) mixing a soluble molybdenum precursor, a sulfur source, and a metal source in a solvent and heating them to react to obtain an angstrom-confined catalyst precursor; (2) Mixing the angstrom-confined catalyst precursor obtained in step (1) with an alkali metal source, heating and calcining the mixture under a reducing atmosphere to obtain the angstrom-confined catalyst.
[0011] In some embodiments of the present invention, in step (1), the soluble molybdenum precursor is selected from one or more of ammonium molybdate, ammonium tetrathiomolybdate or sodium molybdate; The metal source is selected from one or more of an iron source, a copper source, a nickel source, and a cobalt source.
[0012] In some embodiments of the present invention, the sulfur source is selected from one or more of thiourea, sodium sulfide, and sulfur powder.
[0013] In some embodiments of the present invention, in step (1), the temperature of the mixed heating is 180-220° C., and the reaction time is 8-36 h; and the solvent is water.
[0014] The mass ratio of the soluble molybdenum precursor, the sulfur source and the metal source is (35-45): (35-45): (2-8).
[0015] Furthermore, step (1) further comprises drying the product, wherein the drying time is 6-48 h and the drying temperature is 60-90°C.
[0016] In some embodiments of the present invention, in step (2), the alkali metal source is selected from one or more of a sodium source, a potassium source or a lithium salt; The gas of the reducing atmosphere includes hydrogen and inactive gas; The volume content of the hydrogen is 2-10%, and for example, it can be 2 wt%, 3 wt%, 4 wt%, 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt%, 10 wt%, etc.
[0017] Furthermore, the inactive gas is selected from argon and / or nitrogen.
[0018] Furthermore, the alkali metal source is selected from one or more of sodium hydroxide, potassium hydroxide and lithium hydroxide.
[0019] In some embodiments of the present invention, in step (2), the heating and calcining temperature is 700-1000° C. and the time is 1-4 h; The mass ratio of the angstrom-confined catalyst precursor to the alkali metal source is 1:(0.075-2.0).
[0020] Furthermore, the mass ratio of the soluble molybdenum precursor, the sulfur source, the metal source, and the alkali metal source is (35-45): (35-45): (2-8): (12-23).
[0021] Furthermore, step (2) further includes subjecting the product to ultrasonication, centrifugation, dialysis, and drying; The ultrasonic treatment time is 4-12 h; The centrifugation time is 5 min and the rotation speed is 8000 rpm; The drying method is vacuum drying, and the drying time is 6-48 h.
[0022] The third object of the present invention is to provide an Angstrom-confined catalyst for use in wastewater treatment and environmental remediation, wherein the Angstrom-confined catalyst includes the Angstrom-confined catalyst that selectively activates molecular oxygen to produce hydroxyl radicals; the range value of the Angstrom-confined interval is 9 to 13 Angstroms.
[0023] In some embodiments of the present invention, an angstrom-confined catalyst is used to degrade organic pollutants, including sulfonamides (such as sulfamethoxazole), tetracyclines (such as oxytetracycline), and endocrine disruptors (such as bisphenol A, etc.).
[0024] In the present invention, alkali metal cations are embedded in the prepared 2H phase MoS2 loaded with single-atom catalysts to obtain 1T phase MoS2 with different interlayer spacings, and angstrom-scale channels are formed through the interfaces between MoS2 layers, thereby successfully constructing angstrom confined space.
[0025] The above technical solution of the present invention has the following advantages compared with the prior art: 1. The present invention provides an angstrom-confined catalyst, wherein the mass fraction of metal single atoms (such as single-atom iron) in the angstrom-confined catalyst is 0.5-3.0%, and the mass fraction of alkali metal is 0.5-3.0%. The angstrom-confined catalyst provided by the present invention has high HO• yield, high catalytic activity, simple preparation method, and good electrochemical stability.
[0026] 2. Compared with non-angstrom-confined catalysts, the angstrom-confined catalyst provided by the present invention realizes the transformation from a four-electron to a three-electron oxygen reduction process and can selectively generate hydroxyl radicals.
[0027] 3. The angstrom confined catalyst provided by the present invention can achieve the enrichment of HO• in the confined space, thereby achieving efficient removal of target pollutants. The construction of the angstrom confined space can promote the rapid generation of HO• in the confined space, and the yield of HO• is as high as 121 μM·L -1 .
[0028] 4. The present invention provides a method for preparing the above-mentioned angstrom-confined catalyst, comprising the following steps: (1) mixing, reacting, washing and drying a soluble molybdenum precursor, a sulfur source, a metal source and water to obtain an angstrom-confined catalyst precursor; (2) grinding, calcining, ultrasonicating, centrifuging, dialyzing and drying the angstrom-confined catalyst precursor and an alkali metal source to obtain an angstrom-confined catalyst. The dialysis treatment can remove residual alkali metal cations, thereby improving the three-electron selectivity in the oxygen reduction process.
[0029] 5. The Angstrom-confined catalyst provided by the present invention can be used for electrochemical reactions after being loaded on carbon paper, carbon cloth, carbon felt or other conductive current collectors.
[0030] 6. The present invention also provides an angstrom-confined catalyst or an angstrom-confined catalyst prepared by the preparation method for use in wastewater treatment and environmental remediation. The catalyst provided by the present invention can efficiently degrade new pollutants, meeting the needs of economical, flexible and sustainable water purification. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to make the content of the present invention more clearly understood, the present invention is further described in detail below according to specific embodiments of the present invention in conjunction with the accompanying drawings, wherein: Figure 1 is a transmission electron microscope of the Angstrom confined catalyst prepared in Example 1 of the present invention; Figure 2 This is a spherical aberration electron microscope image of the Angstrom confined catalyst obtained in Example 1 of the present invention; Figure 3 It is a quantitative analysis of HO• produced at the cathode of Fe-MoS2 (Comparative Example 1), Li-Fe-MoS2 (Example 3), K-Fe-MoS2 (Example 2) and Na-Fe-MoS2 (Example 1) in 0.05 M Na2SO4 with pH=3 saturated with O2 in Test Example 1 of the present invention; Figure 4 It is the R space data obtained from the Fourier transform (FT) curve of the synchrotron radiation X-ray absorption spectrum of the Angstrom confined catalyst obtained in Example 1 of the present invention and Comparative Example 1. DETAILED DESCRIPTION
[0032] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.
[0033] Example 1 This embodiment provides an Angstrom-confined catalyst, in which the mass fraction of iron is 1.8% and the mass fraction of sodium is 1.5%.
[0034] This embodiment also provides a method for preparing an Angstrom-confined catalyst, comprising the following steps: (1) Preparation of angstrom-confined catalyst precursor: 1.248 g (NH4)2MoO4 and 1.142 g CH4N2S were dissolved in 60 mL of deionized water. Ultrasonic dispersion was performed at room temperature for 10 minutes to make it a uniform and transparent red-brown solution. Then 0.123 g Fe(NO3)3•9H2O was added to the red-brown solution. After stirring and dissolving, the mixed solution was transferred to a 100 mL polytetrafluoroethylene-lined autoclave. The autoclave was then sealed and kept in an oven at 200°C for 24 hours. After the reactor was cooled to room temperature, Fe-MoS2 was washed with deionized water and ethanol respectively to remove the unreacted precursor, and then the Fe-MoS2 sample was dried at 80°C for 24 hours to obtain 2H phase MoS2 powder (i.e., angstrom-confined catalyst precursor).
[0035] (2) Preparation of angstrom-confined catalyst: The 2H phase MoS2 powder obtained in step (1) was ground and mixed with a certain amount of NaOH (mass ratio of 2:1) to obtain a mixture. The mixture was then calcined in an Ar / H2 (H2 volume content of 5%) atmosphere at 800°C for 2 hours. The calcined product was treated in ultrasound for 8 hours. The obtained product was centrifuged at 8000 rpm for 5 minutes to separate the suspension, and then dialyzed using a dialysis membrane to remove residual cations, and finally a 1T phase Na-Fe-MoS2 angstrom-confined catalyst was obtained. The obtained product was structurally characterized, and the results are shown in FIG. Figure 1 , Figure 2 and Figure 4 ,Depend on Figure 1 and Figure 2 It can be seen that after the embedding of alkali metal cations, MoS2 transforms from the 2H phase to the 1T phase, forming an angstrom confined space (about 10.3 angstroms). Figure 4 As shown in the R space data obtained from the Fourier transform (FT) curve of the synchrotron radiation X-ray absorption spectrum of the Angstrom confined catalyst obtained in Example 1 of the present invention, the standard sample iron foil has an obvious Fe-Fe bond at 2.2 Å, Fe2O3 has an obvious Fe-Fe bond at 1.4 Å, and Na-Fe-MoS2 and Fe-MoS2 have Fe-S bonds at 1.8 Å, and there are no Fe-Fe or Fe-O bonds, indicating that the prepared catalyst is a single atom catalyst, rather than a catalyst loaded with a metal element or a metal oxide.
[0036] Example 2 (Compared with Example 1, different alkaline earth metal doping is used) This embodiment provides an Angstrom-confined catalyst, in which the mass fraction of iron is 1.7% and the mass fraction of potassium is 2.0%.
[0037] This embodiment also provides a method for preparing an Angstrom-confined catalyst, comprising the following steps: (1) Preparation of angstrom-confined catalyst precursor: 1.248 g (NH4)2MoO4 and 1.142 g CH4N2S were dissolved in 60 mL of deionized water. Ultrasonic dispersion was performed at room temperature for 10 minutes to make it a uniform and transparent red-brown solution. Then 0.123 g Fe(NO3)3•9H2O was added to the red-brown solution. After stirring and dissolving, the mixed solution was transferred to a 100 mL polytetrafluoroethylene-lined autoclave. The autoclave was then sealed and kept in an oven at 200°C for 24 hours. After the reactor was cooled to room temperature, Fe-MoS2 was washed with deionized water and ethanol respectively to remove the unreacted precursor, and then the Fe-MoS2 sample was dried at 80°C for 24 hours to obtain 2H phase MoS2 powder (i.e., angstrom-confined catalyst precursor).
[0038] (2) Preparation of angstrom-confined catalyst: The 2H phase MoS2 powder obtained in step (1) was ground and mixed with a certain amount of KOH (mass ratio of 1.4:1) to obtain a mixture. The mixture was then calcined in an Ar / H2 (H2 volume content of 5%) atmosphere at 800°C for 2 hours. The calcined product was treated in ultrasound for 8 hours. The obtained product was centrifuged at 8000 rpm for 5 minutes to separate the suspension, and then dialyzed using a dialysis membrane to remove residual cations, and finally a 1T phase K-Fe-MoS2 angstrom-confined catalyst (angstrom confinement space of about 13 angstroms) was obtained.
[0039] Example 3 (Compared with Example 1, different alkaline earth metal doping is used) This embodiment provides an Angstrom-confined catalyst, in which the mass fraction of iron is 1.8% and the mass fraction of lithium is 1.0%.
[0040] This embodiment also provides a method for preparing an Angstrom-confined catalyst, comprising the following steps: (1) Preparation of angstrom-confined catalyst precursor: 1.248 g (NH4)2MoO4 and 1.142 g CH4N2S were dissolved in 60 mL of deionized water. Ultrasonic dispersion was performed at room temperature for 10 minutes to make it a uniform and transparent red-brown solution. Then 0.123 g Fe(NO3)3•9H2O was added to the red-brown solution. After stirring and dissolving, the mixed solution was transferred to a 100 mL polytetrafluoroethylene-lined autoclave. The autoclave was then sealed and kept in an oven at 200°C for 24 hours. After the reactor was cooled to room temperature, Fe-MoS2 was washed with deionized water and ethanol respectively to remove the unreacted precursor, and then the Fe-MoS2 sample was dried at 80°C for 24 hours to obtain 2H phase MoS2 powder (i.e., angstrom-confined catalyst precursor).
[0041] (2) Preparation of angstrom-confined catalyst: The 2H phase MoS2 powder obtained in step (1) was ground and mixed with a certain amount of LiOH (mass ratio of 3.3:1). The mixture was then calcined in an Ar / H2 (H2 volume content of 5%) atmosphere at 800°C for 2 hours. The calcined product was treated in ultrasound for 8 hours. The obtained product was centrifuged at 8000 rpm for 5 minutes to separate the suspension, and then dialyzed using a dialysis membrane to remove residual cations, and finally a 1T phase Li-Fe-MoS2 angstrom-confined catalyst (angstrom confinement space of about 9 angstroms) was obtained.
[0042] Example 4 This embodiment provides an Angstrom-confined catalyst, in which the mass fraction of iron is 1.5% and the mass fraction of sodium is 1.5%.
[0043] This embodiment also provides a method for preparing an Angstrom-confined catalyst, comprising the following steps: (1) Preparation of angstrom-confined catalyst precursor: 1.248 g (NH4)2MoS4 and 1.142 g CH4N2S were dissolved in 60 mL of deionized water. Ultrasonic dispersion was performed at room temperature for 10 minutes to make it a uniform and transparent red-brown solution. Then 0.123 g Fe(NO3)3•9H2O was added to the red-brown solution. After stirring and dissolving, the mixed solution was transferred to a 100 mL polytetrafluoroethylene-lined autoclave. The autoclave was then sealed and kept in an oven at 200°C for 24 hours. After the reactor was cooled to room temperature, Fe-MoS2 was washed with deionized water and ethanol respectively to remove the unreacted precursor, and then the Fe-MoS2 sample was dried at 80°C for 24 hours to obtain 2H phase MoS2 powder (i.e., angstrom-confined catalyst precursor).
[0044] (2) Preparation of angstrom-confined catalyst: The 2H phase MoS2 powder obtained in step (1) was ground and mixed with a certain amount of NaOH (mass ratio of 2:1). The mixture was then calcined at 800°C in an Ar / H2 atmosphere (H2 volume content of 5%) for 2 hours. The calcined product was treated in ultrasound for 8 hours. The obtained product was centrifuged at 8000 rpm for 5 minutes to separate the suspension, and then dialyzed using a dialysis membrane to remove residual cations, thereby finally obtaining a 1T phase Na-Fe-MoS2 angstrom-confined catalyst.
[0045] Example 5 This embodiment provides an Angstrom-confined catalyst, in which the mass fraction of iron is 1.6% and the mass fraction of sodium is 2.1%.
[0046] This embodiment also provides a method for preparing an Angstrom-confined catalyst, comprising the following steps: (1) Preparation of angstrom-confined catalyst precursor: 1.248 g Na2MoO4 and 1.142 g CH4N2S were dissolved in 60 mL deionized water. Ultrasonic dispersion was performed at room temperature for 10 minutes to make it a uniform and transparent red-brown solution. Then 0.123 g Fe(NO3)3•9H2O was added to the red-brown solution. After stirring and dissolving, the mixed solution was transferred to a 100 mL polytetrafluoroethylene-lined autoclave. The autoclave was then sealed and kept in an oven at 200°C for 24 hours. After the reactor was cooled to room temperature, Fe-MoS2 was washed with deionized water and ethanol respectively to remove the unreacted precursor, and then the Fe-MoS2 sample was dried at 80°C for 24 hours to obtain 2H phase MoS2 powder (i.e., angstrom-confined catalyst precursor).
[0047] (2) Preparation of angstrom-confined catalyst: The 2H phase MoS2 powder obtained in step (1) was ground and mixed with a certain amount of NaOH (mass ratio of 2:1). The mixture was then calcined in an Ar / H2 (H2 volume content of 5%) atmosphere at 800°C for 2 hours. The calcined product was treated in ultrasound for 8 hours. The obtained product was centrifuged at 8000 rpm for 5 minutes to separate the suspension, and then dialyzed using a dialysis membrane to remove residual cations, thereby finally obtaining a 1T phase Na-Fe-MoS angstrom-confined catalyst.
[0048] Example 6 This embodiment provides an Angstrom-confined catalyst, in which the mass fraction of iron is 2.5% and the mass fraction of sodium is 1.4%.
[0049] This embodiment also provides a method for preparing an Angstrom-confined catalyst, comprising the following steps: (1) Preparation of angstrom-confined catalyst precursor: 1.248 g (NH4)2MoO4 and 1.142 g CH4N2S were dissolved in 60 mL of deionized water. Ultrasonic dispersion was performed at room temperature for 10 minutes to make it a uniform and transparent red-brown solution. Then 0.246 g Fe(NO3)3•9H2O was added to the red-brown solution. After stirring and dissolving, the mixed solution was transferred to a 100 mL polytetrafluoroethylene-lined autoclave. The autoclave was then sealed and kept in an oven at 200°C for 24 hours. After the reactor was cooled to room temperature, Fe-MoS2 was washed with deionized water and ethanol respectively to remove the unreacted precursor, and then the Fe-MoS2 sample was dried at 80°C for 24 hours to obtain 2H phase MoS2 powder (i.e., angstrom-confined catalyst precursor).
[0050] (2) Preparation of angstrom-confined catalyst: The 2H phase MoS2 powder obtained in step (1) was ground and mixed with a certain amount of NaOH (mass ratio of 2:1). The mixture was then calcined in an Ar / H2 (H2 volume content of 5%) atmosphere at 800°C for 2 hours. The calcined product was treated in ultrasound for 8 hours. The obtained product was centrifuged at 8000 rpm for 5 minutes to separate the suspension, and then dialyzed using a dialysis membrane to remove residual cations, and finally a 1T phase Na-Fe-MoS2 angstrom-confined catalyst was obtained.
[0051] Example 7 This embodiment provides an Angstrom-confined catalyst, in which the mass fraction of iron is 1.5% and the mass fraction of sodium is 2.1%.
[0052] This embodiment also provides a method for preparing an Angstrom-confined catalyst, comprising the following steps: (1) Preparation of angstrom-confined catalyst precursor: 1.248 g (NH4)2MoO4 and 1.142 g CH4N2S were dissolved in 60 mL deionized water. Ultrasonic dispersion was performed at room temperature for 10 minutes to make it a uniform and transparent red-brown solution. Then 0.123 g Fe(NO3)3•9H2O was added to the red-brown solution. After stirring and dissolving, the mixed solution was transferred to a 100 mL polytetrafluoroethylene-lined autoclave. The autoclave was then sealed and kept in an oven at 200°C for 24 hours. After the reactor was cooled to room temperature, Fe-MoS2 was washed with deionized water and ethanol respectively to remove the unreacted precursor, and then the Fe-MoS2 sample was dried at 80°C for 24 hours to obtain 2H phase MoS2 powder (i.e., angstrom-confined catalyst precursor).
[0053] (2) Preparation of angstrom-confined catalyst: The 2H phase MoS2 powder obtained in step (1) was ground and mixed with a certain amount of NaOH (mass ratio of 1.3:1). The mixture was then calcined in an Ar / H2 (H2 volume content of 5%) atmosphere at 800°C for 2 hours. The calcined product was treated in ultrasound for 8 hours. The obtained product was centrifuged at 8000 rpm for 5 minutes to separate the suspension, and then dialyzed using a dialysis membrane to remove residual cations, and finally a 1T phase Na-Fe-MoS2 angstrom-confined catalyst was obtained.
[0054] Example 8 This embodiment provides an Angstrom-confined catalyst, in which the mass fraction of copper is 0.7% and the mass fraction of sodium is 1.5%.
[0055] This embodiment also provides a method for preparing an Angstrom-confined catalyst, comprising the following steps: (1) Preparation of angstrom-confined catalyst precursor: 1.248 g (NH4)2MoO4 and 1.142 g CH4N2S were dissolved in 60 mL of deionized water. Ultrasonic dispersion was performed at room temperature for 10 minutes to make it a uniform and transparent blue solution. Then 0.0561 g Cu(NO3)2•9H2O was added to the red-brown solution. After stirring and dissolving, the mixed solution was transferred to a 100 mL polytetrafluoroethylene-lined autoclave. The autoclave was then sealed and kept in an oven at 200°C for 24 hours. After the reactor was cooled to room temperature, the Cu-MoS2 was washed with deionized water and ethanol respectively to remove the unreacted precursor, and then the Cu-MoS2 sample was dried at 80°C for 24 hours to obtain 2H phase MoS2 powder (i.e., angstrom-confined catalyst precursor).
[0056] (2) Preparation of angstrom-confined catalyst: The 2H phase MoS2 powder obtained in step (1) was ground and mixed with a certain amount of NaOH (mass ratio of 2:1). The mixture was then calcined at 800°C in an Ar / H2 atmosphere (H2 volume content of 5%) for 2 hours. The calcined product was treated in ultrasound for 8 hours. The obtained product was centrifuged at 8000 rpm for 5 minutes to separate the suspension, and then dialyzed using a dialysis membrane to remove residual cations, thereby finally obtaining a 1T phase Na-Cu-MoS2 angstrom-confined catalyst.
[0057] Example 9 This embodiment provides an Angstrom-confined catalyst, in which the mass fraction of nickel is 0.5% and the mass fraction of sodium is 1.5%.
[0058] This embodiment also provides a method for preparing an Angstrom-confined catalyst, comprising the following steps: (1) Preparation of angstrom-confined catalyst precursor: 1.248 g (NH4)2MoO4 and 1.142 g CH4N2S were dissolved in 60 mL of deionized water. Ultrasonic dispersion was performed at room temperature for 10 minutes to make it a uniform and transparent green solution. Then 0.087 g NiNO3•6H2O was added to the red-brown solution. After stirring and dissolving, the mixed solution was transferred to a 100 mL polytetrafluoroethylene-lined autoclave. The autoclave was then sealed and kept in an oven at 200°C for 24 hours. After the reactor was cooled to room temperature, Ni-MoS2 was washed with deionized water and ethanol respectively to remove the unreacted precursor, and then the Ni-MoS2 sample was dried at 80°C for 24 hours to obtain 2H phase MoS2 powder (i.e., angstrom-confined catalyst precursor).
[0059] (2) Preparation of angstrom-confined catalyst: The 2H phase MoS2 powder obtained in step (1) was ground and mixed with a certain amount of NaOH (mass ratio of 2:1). The mixture was then calcined at 800°C in an Ar / H2 atmosphere (H2 volume content of 5%) for 2 hours. The calcined product was treated in ultrasound for 8 hours. The obtained product was centrifuged at 8000 rpm for 5 minutes to separate the suspension, and then dialyzed using a dialysis membrane to remove residual cations, thereby finally obtaining a 1T phase Na-Ni-MoS2 angstrom-confined catalyst.
[0060] Example 10 This embodiment provides an Angstrom-confined catalyst, in which the mass fraction of cobalt is 0.6% and the mass fraction of sodium is 1.4%.
[0061] This embodiment also provides a method for preparing an Angstrom-confined catalyst, comprising the following steps: (1) Preparation of angstrom-confined catalyst precursor: 1.248 g (NH4)2MoO4 and 1.142 g CH4N2S were dissolved in 60 mL of deionized water. Ultrasonic dispersion was performed at room temperature for 10 minutes to make it a uniform and transparent red solution. Then 0.087 g Co(NO3)2•6H2O was added to the red-brown solution. After stirring and dissolving, the mixed solution was transferred to a 100 mL polytetrafluoroethylene-lined autoclave. The autoclave was then sealed and kept in an oven at 200°C for 24 hours. After the reactor was cooled to room temperature, Co-MoS2 was washed with deionized water and ethanol respectively to remove the unreacted precursor, and then the Co-MoS2 sample was dried at 80°C for 24 hours to obtain 2H phase MoS2 powder (i.e., angstrom-confined catalyst precursor).
[0062] (2) Preparation of angstrom-confined catalyst: The 2H phase MoS2 powder obtained in step (1) was ground and mixed with a certain amount of NaOH (mass ratio of 2:1). The mixture was then calcined at 800°C in an Ar / H2 atmosphere (H2 volume content of 5%) for 2 hours. The calcined product was treated in ultrasound for 8 hours. The obtained product was centrifuged at 8000 rpm for 5 minutes to separate the suspension, and then dialyzed to remove residual cations, thereby finally obtaining a 1T phase Na-Co-MoS2 angstrom-confined catalyst.
[0063] Comparative Example 1 (Compared with Example 1, no alkali metal cation intercalation treatment was performed) This comparative example also provides a method for preparing an Angstrom-confined catalyst, comprising the following steps: Preparation of angstrom-confined catalyst precursor: 1.248 g (NH4)2MoO4 and 1.142 g CH4N2S were dissolved in 60 mL deionized water. Ultrasonic dispersion was performed at room temperature for 10 minutes to make it a uniform and transparent reddish-brown solution. Then 0.123 g Fe(NO3)3•9H2O was added to the reddish-brown solution. After stirring and dissolving, the mixed solution was transferred to a 100 mL polytetrafluoroethylene-lined autoclave. The autoclave was then sealed and kept in an oven at 200°C for 24 hours. After the reactor was cooled to room temperature, Fe-MoS2 was washed with deionized water and ethanol, respectively, to remove the unreacted precursor, and then the Fe-MoS2 sample was dried at 80°C for 24 hours to obtain a non-angstrom-confined catalyst. The obtained non-angstrom-confined catalyst was structurally characterized, see Figure 4 . Figure 4 As shown in the R space data obtained from the Fourier transform (FT) curves of the synchrotron radiation X-ray absorption spectra of the Angstrom confined catalyst obtained in Example 1 of the present invention and the non-Angstrom confined catalyst obtained in Comparative Example 1, the standard sample iron foil has an obvious Fe-Fe bond at 2.2 Å, Fe2O3 has an obvious Fe-Fe bond at 1.4 Å, while Na-Fe-MoS2 and Fe-MoS2 have Fe-S bonds at 1.8 Å, and there are no Fe-Fe or Fe-O bonds, indicating that the prepared catalyst is a single atom catalyst, rather than a catalyst loaded with a single metal or a metal oxide.
[0064] Comparative Example 2 (Compared with Example 1, no hydrogen was used during calcination) This comparative example also provides a method for preparing an Angstrom-confined catalyst, comprising the following steps: (1) Preparation of angstrom-confined catalyst precursor: 1.248 g (NH4)2MoO4 and 1.142 g CH4N2S were dissolved in 60 mL of deionized water. Ultrasonic dispersion was performed at room temperature for 10 minutes to make it a uniform and transparent red-brown solution. Then 0.123 g Fe(NO3)3•9H2O was added to the red-brown solution. After stirring and dissolving, the mixed solution was transferred to a 100 mL polytetrafluoroethylene-lined autoclave. The autoclave was then sealed and kept in an oven at 200°C for 24 hours. After the reactor was cooled to room temperature, Fe-MoS2 was washed with deionized water and ethanol respectively to remove the unreacted precursor, and then the Fe-MoS2 sample was dried at 80°C for 24 hours to obtain 2H phase MoS2 powder (i.e., angstrom-confined catalyst precursor).
[0065] (2) Preparation of angstrom-confined catalyst: The 2H phase MoS2 powder obtained in step (1) was ground and mixed with a certain amount of NaOH (mass ratio of 2:1). The mixture was then calcined at 800°C in an Ar atmosphere for 2 hours. The obtained product was centrifuged at 8000 rpm for 5 minutes to separate the suspension, and then dialyzed to remove residual cations, thereby finally obtaining a nanoparticle catalyst NP-Fe-MoS2.
[0066] Test Example 1 The catalysts prepared in Examples 1-10 and Comparative Examples 1-2 were subjected to performance tests, and the content of the performance tests was the yield of HO•. The specific test method is as follows: HO• yield test method: Grind the catalysts prepared in Examples 1-10 and Comparative Examples 1-2, add 0.01 mol of dimethyl sulfoxide (DMSO) and 0.05 mol of anhydrous sodium sulfate (Na2SO4) to 1 L of water, and adjust the pH of the solution to 3 using dilute sulfuric acid. Take 100 mL of the prepared solution and apply a 30 mA constant current to the potentiostat for reaction. The experiment used a two-electrode system, the working electrode was a prepared carbon paper electrode (2.5 cm × 5 cm) loaded with a catalyst, and the counter electrode was a platinum sheet. The electrodes were placed in parallel with a spacing of 2 cm, and oxygen was introduced for 30 minutes in advance. During the reaction, 1 mL of sample was taken every 5 minutes, and 1 mM 2,4-dinitrophenylhydrazine solution was added. The mixed solution was kept warm in a 60°C water bath for 30 minutes and then taken out. Next, the concentration was determined by high performance liquid chromatography. The detection conditions were a water to methanol ratio of 40:60, a detection wavelength of 355 nm, and a flow rate of 0.8 mL min -1 , the peak time is 5.2 minutes.
[0067] The test results are shown in Table 1 below: Table 1
[0068] Conclusion: The catalysts prepared in Examples 1-10 and Comparative Examples 1-2 were tested by rotating disk catalysts, and the hydroxyl radical yields were calculated to be between 11.2 and 121.0. The yield of the optimal sample Example 1 was 121.0 μM·L -1 , and its hydroxyl radical yield is much higher than that of other catalysts.
[0069] Test Example 2 The catalysts prepared in Examples 1-10 and Comparative Examples 1-2 were applied to a simulated polluted wastewater treatment process, and the specific test method was as follows: The indicators of wastewater influent are: 10 mg / L sulfamethoxazole, pH=3, 0.05 M sodium sulfate solution.
[0070] The test method is as follows: the catalyst prepared in Examples 1-10 and Comparative Examples 1-2 is used as the cathode, the platinum sheet is used as the anode, and a degradation test is performed using a constant potentiostat at a constant current of 30 mA, aeration is performed for 30 minutes before the degradation reaction, the oxygen flow rate is 200 mL / min, and the aeration rate is kept constant during the degradation process. After 30 minutes of degradation, sampling is performed, and the sulfamethoxazole content is tested using liquid chromatography.
[0071] The test results are shown in Table 2 below: Table 2
[0072] Conclusion: The catalysts prepared in Examples 1-10 and Comparative Examples 1-2 were respectively subjected to sulfamethoxazole degradation tests, and the sulfamethoxazole removal rates were between 100% and 51.4%. The removal rate of the optimal sample Example 1 could reach 100%, and its sulfamethoxazole removal rate was much higher than that of the catalysts obtained in Comparative Examples 1 and 2.
[0073] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.
Claims
1. An Angstrom-confined catalyst for selectively activating molecular oxygen to produce hydroxyl radicals, characterized in that: 2H phase MoS2 is used as a precursor, the surface of which is loaded with metal single atoms and intercalated with alkali metal cations; the Angstrom confined catalyst is 1T phase MoS2 loaded with metal single atoms.
2. The Angstrom-confined catalyst for selectively activating molecular oxygen to produce hydroxyl radicals according to claim 1, characterized in that: The metal single atom is one or more of iron, cobalt, nickel, and copper; The alkali metal cations include one or more of lithium ions, sodium ions, and potassium ions.
3. The Angstrom-confined catalyst for selectively activating molecular oxygen to produce hydroxyl radicals according to claim 1, characterized in that: The loading amount of the metal single atom is 0.5-3.0 wt %; the loading amount of the alkali metal cation is 0.5-3.0 wt %.
4. A method for preparing an Angstrom-confined catalyst for selectively activating molecular oxygen to produce hydroxyl radicals according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) mixing a soluble molybdenum precursor, a sulfur source, and a metal source in a solvent and heating them to react to obtain an angstrom-confined catalyst precursor; (2) The angstrom-confined catalyst precursor obtained in step (1) is mixed with an alkali metal source, heated and calcined in a reducing atmosphere, dialyzed, and dried to obtain the angstrom-confined catalyst.
5. The preparation method according to claim 4, characterized in that: In step (1), the soluble molybdenum precursor is selected from one or more of ammonium molybdate, ammonium tetrathiomolybdate or sodium molybdate; The metal source is selected from one or more of an iron source, a copper source, a nickel source, and a cobalt source.
6. The preparation method according to claim 4, characterized in that: The sulfur source is selected from one or more of thiourea, sodium sulfide and sulfur powder.
7. The preparation method according to claim 4, characterized in that: In step (1), the temperature of the mixed heating is 180-220°C, and the reaction time is 8-36 h; The mass ratio of the soluble molybdenum precursor, the sulfur source and the metal source is (35-45): (35-45): (2-8).
8. The preparation method according to claim 4, characterized in that: In step (2), the alkali metal source is selected from one or more of a sodium source, a potassium source or a lithium salt; The gas of the reducing atmosphere includes hydrogen and inactive gas; The volume content of the hydrogen is 2-10%.
9. The preparation method according to claim 4, characterized in that: In step (2), the heating and calcining temperature is 700-1000°C and the time is 1-4 h; The mass ratio of the angstrom-confined catalyst precursor to the alkali metal source is 1:(0.075-2.0).
10. Use of an Angstrom-confined catalyst in wastewater treatment and environmental remediation, the Angstrom-confined catalyst comprising the Angstrom-confined catalyst for selectively activating molecular oxygen to produce hydroxyl radicals as claimed in any one of claims 1 to 3.
Citation Information
Patent Citations
Preparation method of sodium intercalation induced high-purity 1T-phase molybdenum disulfide solid hydrogen storage material
CN117756180A
Method for enhancing water electrolysis hydrogen production performance through Pt atom replacement induced MoS2 phase transformation
CN117966175A
Method for producing dispersions of nanosheets
US20170044683A1
Composite materials and processes of manufacturing the same for use as high performance catalysts for water splitting
WO2018013055A1
Cited By
KOH-loaded molybdenum disulfide photo-thermal catalyst as well as preparation method and application thereof
CN120605741A